The driving role of the Cdk5/Tln1/FAKS732 axis in cancer cell extravasation dissected by human vascularized microfluidic models. (September 2021) - Gilardi, Mara; Bersini, Simone; Valtorta, Silvia; Proietto, Marco; Crippa, Martina; Boussommier-Calleja, Alexandra; Labelle, Myriam; Moresco, Rosa Maria; Vanoni, Marco; Kamm, Roger D.; Moretti, Matteo
Abstract: Background: Understanding the molecular mechanisms of metastatic dissemination, the leading cause of death in cancer patients, is required to develop novel, effective therapies. Extravasation, an essential rate-limiting process in the metastatic cascade, includes three tightly coordinated steps: cancer cell adhesion to the endothelium, trans -endothelial migration, and early invasion into the secondary site. Focal adhesion proteins, including Tln1 and FAK, regulate the cytoskeleton dynamics: dysregulation of these proteins is often associated with metastatic progression and poor prognosis. Methods: Here, we studied the previously unexplored role of these targets in each extravasation step using engineered 3D in vitro models, which recapitulate the physiological vascular niche experienced by cancer cells during hematogenous metastasis. Results: Human breast cancer and fibrosarcoma cell lines respond to Cdk5/Tln1/FAK axis perturbation, impairing their metastatic potential. Vascular breaching requires actin polymerization-dependent invadopodia formation. Invadopodia generation requires the structural function of FAK and Tln1 rather than their activation through phosphorylation. Our data support that the inhibition of FAKS732 phosphorylation delocalizes ERK from the nucleus, decreasing ERK phosphorylated form. These findings indicate the critical role of these proteins in driving trans -endothelial migration. In fact, both knock-down experiments and chemical inhibition of FAK dramatically reduces lung colonization in vivo and TEM in microfluidic setting. Altogether, these data indicate that engineered 3D in vitro models coupled to in vivo models, genetic, biochemical, and imaging tools represent a powerful weapon to increase our understanding of metastatic progression. Conclusions: These findings point to the need for further analyses of previously overlooked phosphorylation sites of FAK, such as the serine 732, and foster the development of new effective antimetastatic treatments targeting late events of the metastatic cascade.